Alternative study environments of the university of the Philippines Visayas college of management students - Dureza, Paul; Fernandez, Charmi Margaret; Fresnido, Ma. Veronica Veneranda Q.; Mabaquiao, Shayne Mae; Napila, Febbie Consuelo
"Alternative Study Environments of University of the Philippines in the Visayas, College of Management Students" is the focal point of this research study. The study conducted last January 2009 involved 260 students randomly selected in the aforementioned subdivision. The independent variables were accessibility, affordability and comfort while the dependent variable is the alternative study environments of the University of the Philippines in the Visayas, College of Management Students. A researcher-made questionnaire was used to gather data. The questionnaire is reliable with an alpha of .678. The data was computed using the Statistical Package for social Sciences (SPSS) Software. The statistical tools used were frequency count, mean, and ANOVA set at 0.05 level of significance. The results showed that there was a significant influence in the alternative study environments of the University of the Philippines in the Visayas, College of Management students with regards to the accessibility, affordability and comfort of the vicinity.